2021
DOI: 10.1186/s13018-021-02472-9
|View full text |Cite
|
Sign up to set email alerts
|

Risk factor analysis of pulmonary cement embolism during percutaneous vertebroplasty or kyphoplasty for osteoporotic vertebral compression fractures

Abstract: Objective The purpose of this research is to evaluate the risk factors and incidence of pulmonary cement embolism (PCE) during percutaneous vertebroplasty (PVP) or kyphoplasty (PKP) for osteoporotic vertebral compression fractures (OVCFs) based on postoperative computed tomography (CT). Methods A total of 2344 patients who underwent PVP or PKP due to OVCFs in our spine center were analyzed retrospectively. According to the detection of postoperativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 28 publications
(73 reference statements)
1
15
0
Order By: Relevance
“…This finding is consistent with the reports of Dohm et al (14). However, Zou et al (13) reported that patients who underwent PVP had a significantly increased risk of PCE compared to those who underwent PKP.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This finding is consistent with the reports of Dohm et al (14). However, Zou et al (13) reported that patients who underwent PVP had a significantly increased risk of PCE compared to those who underwent PKP.…”
Section: Discussionsupporting
confidence: 91%
“…In the study by Fadili Hassani et al (19), a higher number of treated vertebrae during the PV procedure was an independent risk factor for the occurrence of intracardiac cement embolism. Zou et al (13) indicated that patients with a thoracic fracture have a significantly increased risk of PCE than do those with a thoracolumbar fracture. In our study, we first analyzed the risk of each vertebra for PCE and found PVP or PKP in the T9 vertebra to be a risk factor for PCE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[90][91][92] Risks linked to cement extrusion from the vertebra into the spinal canal have been found to be markedly increased for VP. 93 No significant difference was reported for subsequent fractures between the procedures. 94 A meta-analysis comparing complications of percutaneous VP and BKP to treat osteoporotic vertebral compression showed no significative differences regarding subsequent fractures.…”
Section: Vertebroplasty and Kyphoplastymentioning
confidence: 91%
“…A combination of questionnaires and consultation of clinical information was utilized, including gender, age, body mass index (BMI), degree of fracture, number of injured vertebrae, BMD, and surgical status, with postoperative telephone follow-up or review ( 15 , 16 ). The degree of fracture was evaluated by Genant semi-quantitative method, including mild fracture, moderate fracture, and severe fracture ( 17 ). Double copies were used to independently enter clinical data, with strict quality control, and timely completion or correction of missing or misreported items to ensure the accuracy and integrity of data.…”
Section: Methodsmentioning
confidence: 99%